Pengaruh Citra Merek, E-WOM dan Customer Rating Terhadap Keputusan Pembelian Skincare Glad2Glow di Kota Batam - Syahrinda Fina; Inda ukati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The increase in consumer interaction with digital platforms and social media has influenced purchasing behavior for beauty products, including skincare. Glad2Glow, as a skincare brand, faces challenges in building trust and making purchasing decisions in Batam City. This study aims to analyze the influence of brand image, E-WOM, and customer ratings on Glad2Glow skincare purchasing decisions. The approach used was descriptive quantitative with a population of active skincare consumers in Batam, and the sample was taken using a purposive sampling technique. A total of 100 respondents who met the research criteria were collected and analyzed. Data analysis was carried out through validity and reliability tests, verification of classical assumptions, and multiple linear regression to examine the influence of independent variables on purchasing decisions. The results showed that brand image, E-WOM, and customer ratings each had a significant and positive influence on purchasing decisions. Brand image contributed 34.3%, E-WOM 16.2%, and customer ratings 55.2%. Simultaneously, these three variables were able to explain 84.3% of the variance in consumer purchasing decisions. Thus, it can be concluded that brand image, E-WOM, and customer ratings, both partially and simultaneously, have a significant influence on the purchasing decision of Glad2Glow skincare in Batam City.